John Prentiss Poe (Editor), The Maryland Code: Public Local Laws, Adopted by the General Assembly of Maryland March 14, 1888, Including Also the Public Local Acts of the Session of 1888 Incorporated Therein 522–23 (Vol. 1, 1888), ch. 187, § 742 - (:unkn) unknown (General Publisher, 1884)
Sentencing enhancement for drunk or disorderly conduct, or beach of peace. Concealed Carrying of any pistol, dirk, Bowie-knife, sling-shot, billy, metallic knuckles, razor, or any other deadly weapon whatsoever. Violators subject to fine of not less than five but no more than twenty-five dollars, confiscation of the weapon.
--
Keywords: CARRY - CONCEALED